Comparison of Plantar Pressure Distribution and Vertical Ground Reaction Force between Dominant and None-Dominant Limb in Healthy Subjects Using Principle Component Analysis (PCA) Technique - Abbas Farjad-Pezeshk; Heydar Sadeghi; Maedeh Farzadi (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: The aim of this study was the comparison of plantar pressure distribution and vertical ground reaction force between dominant and none-dominant limbs in healthy through using Principle Component Analysis (PCA) technique. Materials & Methods: This study was quasi-experimental in which 20 healthy adult males and females were selected from available subjects. Subject's plantar pressure distribution and vertical ground reaction force measured using the Pedar-X system. The obtained data were analyzed by Paired-t test, one way analyze of variance, Pearson coefficient correlation and PCA. Results: ANOVA and Paired-t test did not show any significance difference between males and females and dominant and non-dominant limb pressure pattern, (P>0.05). PCA recognized pressure and force applied on the heel, fingers, big toe and first metatarsal regions for the dominant limb and lateral mid foot, lateral fore foot, first metatarsal and heel regions for non-dominant limb, as important parameters. Conclusion: The results of this study showed that, dominant limb is responsible for propulsion and weight acceptance and non-dominant limb is responsible for balance control. Therefore during biomechanical evaluation of feet, difference between function of dominant and non-dominant limb must be considered.